2020
DOI: 10.1186/s40463-020-00436-3
|View full text |Cite
|
Sign up to set email alerts
|

Designing and integrating a quality management program for patients undergoing head and neck resection with free-flap reconstruction

Abstract: Background: Care pathways (CPs) offer a proven method of systematically improving patient care. CPs are particularly helpful in complex clinical conditions where variation in care is a problem such as patients undergoing major head and neck resection with free flap reconstruction. Although CPs have been used to manage this patient group, most CPs are implemented as part of relatively short-term quality improvement projects. This paper outlines a detailed methodology for designing and delivering a quality manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…Leading change activities included having a sponsor or champion and team members who demonstrated visible, active, public commitment and were supportive of the change. Dort 36 2020 Quantitative Eight KPIs Academic Teaching Hospital, Canada Head and Neck surgery Department Kotter’s 8-Step Process Outline and describe a quality management program Demonstrated sustained high clinical performance when compared to a non-pathway managed cohort using 7 years of prospective outcomes data. Dredge 37 2017 Mixed Methods Working party and survey Calvary Health Care Bethlehem community palliative care service, NSW, Australia Nurses in an outpatient palliative care service Kotter’s 8-step To change anticipatory medicine practices in palliative care Study identified carers found it difficult to attend training however, found the step by step instructions useful to administer medicines in a timely manner without a nurse.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Leading change activities included having a sponsor or champion and team members who demonstrated visible, active, public commitment and were supportive of the change. Dort 36 2020 Quantitative Eight KPIs Academic Teaching Hospital, Canada Head and Neck surgery Department Kotter’s 8-Step Process Outline and describe a quality management program Demonstrated sustained high clinical performance when compared to a non-pathway managed cohort using 7 years of prospective outcomes data. Dredge 37 2017 Mixed Methods Working party and survey Calvary Health Care Bethlehem community palliative care service, NSW, Australia Nurses in an outpatient palliative care service Kotter’s 8-step To change anticipatory medicine practices in palliative care Study identified carers found it difficult to attend training however, found the step by step instructions useful to administer medicines in a timely manner without a nurse.…”
Section: Methodsmentioning
confidence: 99%
“…Step Model for managing change, with one further study that integrated the Kotter model with Silversin and Kornacki's model. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] Eight studies referenced their application of the Lewin 3-Stage Model of Change into a healthcare setting, [48][49][50][51][52][53][54][55] with three further studies that integrated the Lewin model with a concern-based change management approach, McKinsey 7S Model of Change, and Roger's Diffusion of Innovation Theory, respectively. [56][57][58] A further eight articles reported the use of six further models for managing and leading change: Influencer Change Model (1 study); 59 Prosci ADKAR (1 study); 60 Accelerated Implementation Methodology (AIM) (2 studies); 61,62 Advent Health Clinical Transformation Model (1 study); 63 Riches 4 stage model (1 study); 64 Youngs Nine Stage Framework (1 study), 65 and the CAP model (1 study).…”
Section: Most Of the Studies Utilised Either Kotter's 8-step Model (1mentioning
confidence: 99%
See 1 more Smart Citation
“…Two patient groups were compared. A pre-MMA cohort that included patients who underwent surgery between January 2015–December 2015 and were managed using the Calgary Head and Neck Enhanced Recovery Program (CHERP) protocol [ 4 , 17 , 18 ]. The MMA cohort included all patients who underwent surgery between December 2017–June 2019 and received the CHERP protocol plus additional ERAS elements including treatment with MMA.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently conducted a feasibility study 30,42 within the Calgary Head and Neck Enhanced Recovery Program 4,43 to add WATs to the postoperative period. A wrist-worn WAT (Garmin vívofit®4) was provided on POD 1 following major HNC surgery with free flap reconstruction.…”
Section: Introducing Wearable Activity Trackers To An Enhanced Recovery Pathway For Head and Neck Cancermentioning
confidence: 99%